Proyecto de prefactibilidad para desarrollar una nueva unidad de negocio de moda en la empresa Jukapa SAS en Bogotá - Parrado Mesa, Edwin Orlando (Universidad Antonio Nariño, 2022)
The present project compiles the investigation, where a strategy is proposed to open a new market segment in the Jukapa company as a positioning mechanism in the market, Jukapa located in the Galán neighborhood of B ogotá based on population inquiry tools, such as surveys, analyzed the potential market and the different variables of production, suppliers and customers. The research has four secondary objectives that are presented throughout the document, in which surv eys are taken from primary sources such as the population in Bogotá, for the collection of data and important information for the approach of the strategy. For this project, the aim is to contextualize the impact that fashion has had in Colombia, and later an investigation is carried out that aims to reveal the possibility of creating a clothing brand within the Bogota community. The central concepts (fashion, consumption, identity and target audience), which will be redefined and articulated, as they are n ecessary to analyze the feasibility of creating a new market segment in the company Jukapa SAS.